Types of Geoecosystems of the Lobelia Lakes of the Tricity Area - Markowski, Maciej; Kwidzińska, Monika (Quaestiones Geographicae, 2015)
In the years 2009-2010 limnological research was carried out on 13 lobelia lakes of the Tricity metropolitan area. These lakes, of unique value not only on the scale of the country, are undergoing degradation due to increasing anthropogenic pressure. Grade of degradation of these lakes, depends on geoecosystem type, which they are representing. Geoecosystem type of the lake, defines the rate of natural eutrophication of reservoir. In this article types of geoecosystems of analysed lobelia lakes where defined in accordance with the guidelines of Bajkiewicz-Grabowska (1981, 1983, 1985, 1987, 2002). The obtained results indicate that only one of the analysed lakes (Zawiat Lake) is likely to retain a low trophic level. Four lakes (Głębokie, Kamień, Borowo, Techlinko) represent geoecosystems with a moderate rate of natural eutrophication. The remaining of the analysed lobelia lakes are threatened with fast water eutrophication, which is demonstrated by a high catchment vulnerability to activate areal load, and a low resistance of the lakes (resulting from their natural properties) to external supply. The obtained results correspond to field measurements and make it possible to indicate actions aimed at protecting the group of the analysed lobelia lakes.